SOCIAL MEDIA AND MENTAL HEALTH - Siwach, Kuldeep; K Singh, Meenakshi (International Journal of Psychosocial Rehabilitation, 2020)
Social media, communally, has become the mental food for the human mind. All through the past decade, online social networking has precipitated profound changes in the manner humans communicate, consume, and engage. Several researchers have indicated that the extended use of social networking, which includes Facebook, Twitter, and WhatsApp, can be related to indications and symptoms of melancholy. Several studies have established a solid association between substantial social media usage and an amplified risk for sadness, unhappiness, apprehension, lonesomeness, and even suicidal thoughts. In addition, a few authors have indicated that certain social network sites sport is probably associated with low vanity, especially in children and teens. The present paper, with the help of primary and secondary data, is trying to excavate that the excessive use of social media puts negative effects on the mental health of the operative user. The present study was an attempt to examine the association between social media consumption and mental construction among the youth. Furthermore, to quantify the responses from the sample of 100 active social media users, college students were scanned. Upshots revealed a substantial negative association between excessive usage and mental state.